Aggregates stability and resistance in Dark-Red Latosol (Oxisol) under corn-green manure succession - Leandro Naves Silva, Marx; Blancaneaux, Philippe; Curi, Nilton; Maria de Lima, José; José Granate de Sá e Melo Marques, João; Moreira de Carvalho, Armida (Pesquisa Agropecuaria Brasileira, 1998)
Latosols (oxisols) under cerrado vegetation in their natural condition present, in general, high structural stability due mainly to the performance of aluminum and iron oxides and organic matter. In the Cerrado region, however, the practice of burning cultural residues and the excessive use of harrow during soil preparation is very common, mainly the plowing harrow, which pulverizes the soil with consequent weakness and destruction of soil structure. This study aimed to evaluate the resistance of aggregates of a cerrado phase, clayey texture, Dark-Red Latosol (Oxisol) to simulated raindrop impact as well as the geometrical average diameter of aggregates of this soil under different green manure-corn succession systems and under native cerrado. The tested green manure species were Crotalaria juncea, Cajanus cajan, Mucuna aterrima, Brachiaria ruziziensis and Canavalia ensiformis, cultivated in rotation with corn (cv. Pioneer 3072), during two years. The native cerrado presented larger and more stable aggregates, and it was necessary higher kinectic energy for disrupting them. In the green manure systems, brachiaria showed higher aggregation action than the leguminous species. The simulated raindrop impact method presented good performance, leading to better distinction among the treatments in relation to the aggregates stability method.